IDENTIFIKASI FAKTOR FAKTOR STRATEGIS DALAM RANGKA PEMBUATAN PERENCANAAN PEMBANGUNAN PARTISIPASI DESA PAKIS MOJOKERTO JAWA TIMUR - Bambang Agoes Hermanto; Asfi Manzilati; Ghozali Maski; Munawar Ismail (Universitas Prof. Dr. Hazairin SH, 2021)
The purpose of this study is to identify strategic factors in the framework of making participatory development planning in thevillage of Pakis Mojokerto, East Java. The methodology used in this research is descriptive qualitative using SWOT analysis. The results of the study show that the actors of strengths and opportunities greatly contribute to strategic determination, so thestrategy used is to optimize strengths in seizing opportunities. The strategy is to increase human resources (including improving health and education infrastructure and facilities), increase access to financial institutions or credit for productive business development, develop non-agricultural businesses that are still related to the agricultural sector, and develop village tourism. The implications of this research are The strategy used in participatory development planning is to strengthen strengths toovercome weaknesses